Civil society participation in the Scottish marine planning process and the role of Environmental Non-Governmental Organisations. Issue 12 (15th October 2019) - Brooker, E.E.; Hopkins, C.R.; Devenport, E.; Greenhill, L.; Duncan, C.
Abstract : Sustainable development principles are based on the fundamental recognition of humans as an integral part of the ecosystem. Participation of civil society should therefore be central to marine planning processes and enabling ecosystem-based management, and development of mechanisms for effective participation is critical. To date, little attention has been given to the role of Environmental Non-Governmental Organisations (ENGOs) in public participation. In this paper, the results of two workshops, which involved various stakeholders and addressed public participation in marine planning, are reported and discussed in the context of the Scottish marine planning process. ENGOs' role in communicating complex policies, representing members' interests and contributing towards participatory governance in marine planning is highlighted. Innovative outreach methods are still required by decision-makers to translate technical information, integrate local knowledge, improve public representation and conserve resources. This could include collaboration with ENGOs to help promote public participation in decision-making processes.